DYNAMIC MONITORING OF FRICTIONAL MOBILE SYSTEMS TRIBOTHERMODYNAMICS - Andrey L. Ozyabkin (Advanced Engineering Research, 2011)
A hypothesis of experimental tribothermodynamics had been suggested and proved. The hypothesis permits to define flash temperature on the true contact area as a practical example.